Economic Care Day: Training Leadership, Creativity, Collaboration, and Sociopreneur at Smk Negeri 1 Merangin 2024 - Sarinah, Sarinah; Mardalena, Mardalena; Melina, Angra; Andriani, Diyan; Utami, Sri; Afika, Tya (Society : Jurnal Pengabdian Masyarakat, 2025)
The purpose of the Economic Care Day 2024 program at SMK Negeri 1 Merangin is to foster student leadership, creativity, teamwork, and sociopreneurship. Utilizing several interactive training sessions, practical exercises, and realistic business simulations, this program seeks to equip students to become creative and socially conscious entrepreneurs. Four major areas are the program's focus: The first is Leadership Development, which teaches students how to make decisions, solve problems, and manage a team; the second is Creativity Enhancement, which promotes creative thinking and solution-based entrepreneurship; the third is Collaboration Training, which stresses teamwork and good communication; and the fourth is Sociopreneurship Education, which introduces the idea of business models that put profit and social.  Economic Care Day 2024 reaches 146 students as participants aim to equip students with strong social entrepreneurship knowledge, enhanced leadership, teamwork abilities, and an expanded entrepreneurial attitude. Through experiential learning, workshops, case studies, and mentorship, students are equipped to contribute to their communities and the global economy